Kelestarian bandar sebagai habitat manusia - Abdul Hadi Harman Shah; Abdul Samad Hadi; Shaharudin Idrus; Ahmad Fariz Mohamed (Universiti Kebangsaan Malaysia, 2010)
The current focus of discussion on sustainable development centres around the various implementations of an agenda that is assumed to be accepted by all. Various proposals at the international level are accepted and implemented by various agencies at the local level many times without taking the local context into consideration. The assumption of uniformity, or at least similarity of values and priorities of cities drive current public and funding concerns. What is emphasized is the contribution of cities towards the problem and solution of global sustainable development. While the premise is based on good intentions, such an approach also invites contradictions between two different scales of values and viewpoints. The paper discusses the meanings and implications of the sustainable city, a central concern of the sustainable development agenda in Malaysia and internationally. It argues that the choice of definition for sustainability will influence the approach that a city is planned, expanded and evaluated. All impact directly upon the daily life of local residents with a culture and problems that are often different from those perceived at the international level. Finally the paper questions whether local identity and importance can still be defended in the increasing acceptance of a global agenda such as that of sustainable development